SUSTAINABLE FARMING MODEL ACCORDING TO THE SUFFICIENCY ECONOMY CONCEPT BAN THON-OM, CHONG MAI KAEW SUBDISTRICT, THUNG TAKO DISTRICT, CHUMPHON PROVINCE - Thepsut , Chanchanok (Journal of MCU Nakhondhat, 2025)
The purpose of this article is to 1) Study the context, problem situations, and farming management, and 2) To find sustainable farming models based on the Sufficiency Economy concept Ban Thon-Om, Chong Mai Kaew Subdistrict, Thung Tako District, Chumphon Province. The Mixed Methods, quantitative Research, sample groups consisting: of community members or families, farmers, and community leaders or leaders, purposive sampling, a total of 30 people. The research tools include: a questionnaire, used for analyzing percentage, mean, and standard deviation. In qualitative Research, key informants include: The community enterprise committee, store management committee, relevant institutions, and small members of the enterprise, purposive sampling, a total of 15 people. The research tools include: in-depth interviews and focus groups and descriptive content analysis. The research found that: The original community context is Khao Ma Haeng Village, Moo 2, and in 1997, divided into Ban Thon-Om Village in Moo 6, and is a model community of the Sufficiency Economy. The problem situations include: 1) Production planning, 2) Finance and accounting, 3) Production, 4) Marketing, 5) Group management, 6) Environment, 7) Community resources, and 8) Knowledge management. The sustainable farming models based on the Sufficiency Economy, with self-reliant agricultural management, emphasizing safety, and creating a balance between the ecosystem and the environment include: 1) Moderation, 2) Reason, 3) Immunity, 4) Knowledge, and 5) Morality. And find sustainable farming models based on the Sufficiency Economy, self-reliant farming management, emphasizing safety, and creating a balance between the ecosystem and the environment include: 1) Ecological consistency, 2) Economic feasibility, 3) Social justice, 4) Humanization, and 5) Resilience. The factors of sustainable farming include: participation, agricultural partnerships, being environmentally friendly, community well-being, and knowledge management.